Ligas acadêmicas : perfil discente e produção dos participantes - Goergen, Diego Inácio (2023)
INTRODUCTION: Academic leagues are student groups, under supervision of a professor, formatted in a regular university extension program, present in almost all Brazilian medical schools. They have different activities, in the Teaching, Research and Extension, described in several experience reports. The influence of the leagues in the training of future doctors still lacks in-depth academic studies. OBJECTIVES: To describe the activities of academic leagues and the characteristics of the students, correlating participation in leagues with sociodemographic characteristics, scientific production, academic performance and the recommendation for participation in academic leagues. METHODS: Exploratory and descriptive cross-sectional study, divided in two parts.Initially, an analysis of the activities of the academic leagues was made, dividing into categories. Afterwards, through an online questionnaire directed to students in the last two years of graduation at the PUCRS School of Medicine, in January and February 2022, information was collected regarding sociodemographic characteristics, academic production variables, and degree of recommendation through Net Promoter Score (NPS). For descriptive analysis, categorical variables were expressed as mean and standard deviation or median and interquartile interval, and categorical variables by absolute and relative frequency. Linear correlations were verified by Pearson's test and planned comparison between groups with tests for parametric or nonparametric data according to presentation. RESULTS: Of the 52 active leagues at PUCRS, 27 (51.9%) provided data. The average number of students was 21.6 (± 10.4) per league. Most of them (77.8%) had only one teacher, with some reaching three. The activities raised were mainly theoretical classes, discussion of clinical cases, practical activities, production of scientific articles, publications on social networks, solidarity activities and organization of own events. Seventy-one students participated (36.4% of the total population). On average, each student participated in 3.56 (± 1.55) leagues. Students who were already in their sixth grade, who had published an article, or who had average grades above 8.6 reported participation in a significantly higher average number of leagues. The more leagues the student participated and the more satisfied he was with them, the more he recommended participation to other students. In addition to the leagues, the average participation in different complementary activities by students was 3.00 (± 1.01) activities, especially internships, tutoring, volunteering, and scientific initiation. The average number of papers published was 1.12 (±1.35), with 31 students (43.66%) without publications. The 7 correlation between the number of leagues per student and published papers was positive, with a Pearson correlation coefficient of 0.89. CONCLUSIONS: Students usually enter academic leagues early, participating in many leagues, in addition to participating in other complementary activities. Participation in leagues is associated with more complementary activities and the publication of scientific papers. Leagues can function as a support group for students’ socialization and also work as a peer mentoring group. Satisfied academics recommend participation to their peers, creating a cycle of increased participation among students. In general, leagues are complementary activities that have a positive contribution on the training of medical students